Measuring negative emotional responses to climate change among young people in survey research: A systematic review - Martin, Gina; Cosma, Alina; Roswell, Tasha; Anderson, Martin; Treble, Matthew; Leslie, Kathleen; Card, Kiffer G; Closson, Kalysha; Kennedy, Angel; Gislason, Maya (Social science & medicine (1982), 2023)
BACKGROUND: Climate change is a threat to the mental and emotional wellbeing of all humans, but young people are particularly vulnerable. Emerging evidence has found that young people's awareness of climate change and the danger it poses to the planet can lead to negative emotions. To increase our understanding about this, survey instruments are needed that measure the negative emotions young people experience about climate change. RESEARCH QUESTIONS: (1) What survey instruments are used to measure negative emotional responses to climate change in young people? (2) Do survey instruments measuring young people's negative emotional responses to climate change have evidence of reliability and validity? (3) What factors are associated with young people's negative emotional responses to climate change? METHODS: A systematic review was conducted by searching seven academic databases on November 30, 2021, with an update on March 31, 2022. The search strategy was structured to capture three elements through various keywords and search terms: (1) negative emotions, (2) climate change, and (3) surveys. RESULTS: A total of 43 manuscripts met the study inclusion criteria. Among the 43 manuscripts, 28% focused specifically on young people, while the other studies included young people in the sample but did not focus exclusively on this population. The number of studies using surveys to examine negative emotional responses to climate change among young people has increased substantially since 2020. Survey instruments that examined worry or concern about climate change were the most common. CONCLUSION: Despite growing interest in climate change emotions among young people, there is a lack of research on the validity of measures of such emotions. Further efforts to develop survey instruments geared to operationalize the emotions that young people are experiencing in relation to climate change are needed.
Keywords: Surveys; Surveys and Questionnaires; Humans; Emotions; lidé; Adolescents; reprodukovatelnost výsledků; klimatické změny; průzkumy a dotazníky; Climate Change; Reproducibility of Results; Adolescent; emoce; Psychometrics; Youth; Climate change; Measurement; psychometrie; mladiství